Relation Characteristics of Mother, ANC And Compliance of Maternity With Preeclampsia - Faiqoh, Elok; Hendrati, Lucia (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTPreeclampsia is a hypertensive disorder in pregnancy which is accompanied by edema and proteinuria. This study aimed to analyze the characteristic of mothers, ANC visits and compliance maternity care of preeclampsia in dr. Mohamad Soewandhie Surabaya. This study is using case control with quantitative approach. Samples are 70 people who were taken by simple random sampling method with the distribution of samples 35 cases and 35 controls. The independent variables were age, history of hypertension, history of preeclampsia, primigravida, ANC and compliance of maternity care (provision of preeclampsia information, sources of information, advisory and compliance to suggestions). Data analysis was performed using Chi-Square test. The results showed that the variables are age-related (p = 0.014; OR 5.167), history of preeclampsia (p = 0.000), compliance of maternity care which includes the provision of preeclampsia information (p = 0.000), resources (p = 0.000; OR 0.045 ), provision of advice (p = 0.000; OR 0.015) and compliance of mother to advice (p = 0.000; OR 0.028). Unrelated variables is a history of hypertension (p = 0.198; OR 5.667), primigravida (p = 0.791; OR 0.755), and ANC (p = 0.733; OR 1.603). To reduce the occurrence of severe preeclampsia health workers are expected to be motivating mothers to provide relevant health education and knowledge relevant to the prevention of preeclampsia on the safe age to get pregnant and give birth, how to maintain their health with proper diet, adequate rest, regular medication given, examination timetable next ANC and other suggestions which is may help prevent or reduce the risk of preeclampsia.Keywords: preeclampsia, age, history of preeclampsia, compliance